2021
DOI: 10.1016/j.aninu.2021.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Nano-sized zinc addition enhanced mammary zinc translocation without altering health status of dairy cows

Abstract: This study aimed to evaluate role of nano-sized zinc (Zn) on lactation performance, health status, and mammary permeability of lactating dairy cows. Thirty multiparous dairy cows with similar days in milk (158 ± 43.2) and body weight (694 ± 60.5 kg) were chosen based on parity and milk production and were randomly assigned to 3 treatment groups: basal diet (control, 69.6 mg/kg of Zn adequate in Zn requirement), basal diet additional Zn-methionine (Zn-Met, providing 40 mg/kg of Zn), and basal diet additional na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
1
1
Order By: Relevance
“…Increasing post-ruminal Met in ewes resulted in an evident decline in MDA plasma levels, as observed in the current experiment ( 68 ). The outcome of this experiment was in contrast to previous reports in which supplementing the diet of dairy cows with Zn-Met did not show any significant effect on blood MDA or TAS levels ( 69 ). Oxidative stress is one of the contributing factors to the impairment of the immune responses during environmental stress.…”
Section: Discussioncontrasting
confidence: 99%
“…Increasing post-ruminal Met in ewes resulted in an evident decline in MDA plasma levels, as observed in the current experiment ( 68 ). The outcome of this experiment was in contrast to previous reports in which supplementing the diet of dairy cows with Zn-Met did not show any significant effect on blood MDA or TAS levels ( 69 ). Oxidative stress is one of the contributing factors to the impairment of the immune responses during environmental stress.…”
Section: Discussioncontrasting
confidence: 99%
“…Supplementation of nano ZnO, in vitro, showed an improvement in the growth of ruminal microorganisms, ruminal microbial protein synthesis, and energy utilization efficiency in the early phase of incubation (Zhisheng, 2011). Cai et al, (2021) reported that nano ZnO supplementation improved Zn bioavailability without affecting milk yield, health status, and mammary gland permeability in dairy cows. Nano Zn also increased blood Zn levels and immunity in Zndeprived goats (Song et al, 2021).…”
Section: Bioavailability Of Trace Minerals In Dairy Animalsmentioning
confidence: 99%